Pengaruh Pengetahuan Produk Dan Prinsip Syariah Islam Terhadap Minat Memilih Bank Syariah - Alamatus Saadah; Arief Widyananto (LPPM Universitas Islam 45, 2023)
This study aims to determine the effect of product knowledge and Islamic principles on Islamic banks by describing employee responses to Islamic banking. The research method used qualitative with the research sample being employees and teaching staff at Teratai Putih Global Vocational School 3 and 4 Bekasi, because the school cooperates with the BNI Syariah bank. Data collection techniques by distributing questionnaires, then analyzed using multiple regression analysis techniques. The results of the study show that the products and principles of Sharia contained in Islamic banks have the same positive and significant effect partially and simultaneously on the intention to choose an Islamic bank.